Evapo-transpiration of sesame (Sesamum indicum) in relation to pan evaporation - RAO, V PRAVEEN; RAIKHELKAR, S V (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during summer season of 1988 and 1989 to measure the evapo-transpiration of sesame (Sesamum indicum L.) and relate it to pan evaporation. The treatments comprised 3 levels each of irrigation (0.6. 0.9 and 1.2 irrigation water depth: cumulative pan evaporation ratio) and nitrogen (0. 40 and 80 kg N/ha) and phosphorus (0. 13 and 26 kg P/ha). Ratios of evapo-transpiration to pan evaporation were computed for specific crop-growth phases. viz establishment. vegetative. flowering and capsule initiation. and seed-filling and ripening stages. The average evapo transpiration : pan evaporation ratios were small (0.430) during the establishment phase. increased gradually with crop development (0.680) and attained peaks at flowering and capsule-initiation stages (0.841); thereafter they declined towards seed-filling and ripening stages (0.437). For different treatments each higher level of irrigation water depth: cumulative pan evaporation ratio. N and P increased the evapa-transpiration: pan evaporation ratio. But the magnitude of increase with each higher level was more with irrigation water depth: cumulative pan evaporation ratios. followed by and N and P. A curve fitted to the evapo-transpiration : pan evaporation ratios indicated that the water use by sesame depends on crop development. The relationship may be used to estimate evapo-transpiration of seame and actual irrigation requirement.